Third degree - Iles, Greg. (New York : Scribner, 2007)
A tale spanning a traumatic single day follows Liz Pike, who awakens in her small-town home to discover her husband frantically preparing for what he claims is an IRS audit. She soon realizes, however, that he has discovered the truth about her affair with another man.
Keywords: Family secrets -- Fiction; Mississippi -- Fiction; Suspense fiction